2009
DOI: 10.1002/j.2162-6057.2009.tb01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Trick‐or‐Treat Candy‐Getters and Hornet Scare Devices: Second Graders Make Creative Inventions Related to Animal Adaptations

Abstract: This repeated measures study examined second graders' (n = 21) performance in creating inventions related to animal adaptations for simple products under two conditions that alternated each week for a six-week period. In the analogy condition, students used form and function analogy object boxes to learn about animal adaptations, applying these concepts with the SCAMPER technique to generate a new product with a given item. In the traditional condition, students learned about animal adaptations through text/In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Until now, regular schools have neglected to encourage students who have innate creativity to be innovative and produce new inventions. Rule et al (2009) state that published research on efforts to improve children's inventive skills, especially at the secondary level, is almost nonexistent. Students must not be overlooked, but their latent ability to invent something new should be developed and supported at the national level.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Until now, regular schools have neglected to encourage students who have innate creativity to be innovative and produce new inventions. Rule et al (2009) state that published research on efforts to improve children's inventive skills, especially at the secondary level, is almost nonexistent. Students must not be overlooked, but their latent ability to invent something new should be developed and supported at the national level.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, inventions are being used more to teach many disciplines. Several studies suggest that educational invention helps students gain content knowledge in subject areas (Westberg, 1996;Plucker and Gorman, 1999;Rule et al, 2009). In addition, Plucker and Gorman (1999) have suggested that teaching to invent plays a positive role in both learning and motivation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations